Perioperative gabapentin and post cesarean pain control: A systematic review and meta-analysis of randomized controlled trials. (February 2019) - Felder, Laura; Saccone, Gabriele; Scuotto, Sergio; Monks, David T.; Carvalho, Jose C.A.; Zullo, Fulvio; Berghella, Vincenzo
Abstract: Cesarean delivery occurs in roughly one third of pregnancies. Effective postoperative pain control is a goal for patients and physicians. Limiting opioid use in this period is important as some percentage of opioid naïve individuals will develop persistent use. Gabapentin is a non-opioid medication that has been used perioperatively to improve postoperative pain and limit opioid requirements. The goal of this study is to determine the efficacy of perioperative gabapentin in improving post cesarean delivery pain control. The following data sources were searched from their inception through October 2018: MEDLINE, Ovid, ClinicalTrials.gov, Sciencedirect, and the Cochrane Library at the CENTRAL Register of Controlled Trials. A systematic review of the literature was performed to include all randomized trials examining the effect of perioperative gabapentin on post cesarean delivery pain control and other postoperative outcomes. The primary outcome was the analgesic effect of gabapentin on post cesarean delivery pain, measured by visual analog scale (VAS; 0–100) or Numerical Rating Scale (NRS; 0–10) on movement 24 hours (h) postoperative. These scores were directly compared by multiplying all NRS scores by a factor of 10. Meta-analysis was performed using the random effects model of DerSimonian and Laird, to produce summary treatment effects in terms of mean difference (MD) with 95% confidence interval (CI). Six placebo controlled trials (n = 645) were identified as relevant and included in the meta-analysis. All studies included only healthy pregnant women (American Society of Anesthesiologist (ASA) physical status I or II) undergoing spinal anesthesia for cesarean delivery at term. Participants were randomized to either 600 mg oral gabapentin or placebo preoperatively and in one study the medications were also continued postoperatively. Pooled data showed that women who received gabapentin prior to cesarean delivery had significantly lower VAS pain scores at 24 h on movement (MD -11.58, 95% CI -23.04 to -0.12). VAS pain scores at other time points at rest or on movement were not significantly different for those who received gabapentin and placebo although there was a general trend toward lower pain scores for women receiving gabapentin. There was no significant between-group difference in use of additional pain medications, supplemental opioids, and maternal or neonatal side effects. There was higher pain control satisfaction at 12 and 24 h in the gabapentin versus placebo groups.